Retroperitoneal Abscess: A Rare Localization of Tubercular Infection - Sami Karoui; Norsaf Bibani; Afef Ouaz; Meriem Serghini; Faouzi Chebbi; Kais Nouira; Ines Chelly; Jalel Boubaker; Zoubeir Ben Safta; Emna Menif; Moncef Zitouna; Azza Filali (Gastroenterology Research and Practice)
Incidence of tuberculosis infection has considerably increased during the past 20 years due to the HIV pandemic and continues to be one of the most prevalent and deadly infections worldwide. Extrapulmonary tuberculosis lacks specific clinical manifestation and can mimic many diseases. It can invade neighbouring tissue and form a big cyst with manifesting clinical symptoms. We describe a rare case of 31-year-old immunocompetent man affected by a retroperitoneal abscess secondary to tubercular infection. Exploratory laparotomy and histopathological examinations of tissue were required for achieving diagnosis of tuberculosis. No pulmonary or spinal involvement was identified. The patient was successfully treated with standard four-drug antitubercular therapy.